Effects of problem-solving approach on problem-solving skills, motivation, and writing achievement of middle-eastern EFL learners - Hussein, Hawanum (2014)
This quasi-experimental research examined the effects of the problem-solving approach (PSA) on perceived problem-solving skills, motivation and writing achievement of International students who were EFL learners in an intensive English program. A quantitative method approach with a sample size of 57 students was used to collect and analyze the data. Qualitative data collected from a standardized reflection worksheet and a focus group interview was also obtained to support, explain and strengthen the quantitative findings. In this post-test control group research design, two intact Intermediate classes of EFL learners were randomly assigned as the treatment and the control group. Both groups were given ill-structured problems to solve but only the treatment group received the problem-solvingapproach (PSA). The PSA incorporated the problem-solving technique used in problem-solving learning (PBL) with elements of the process approach to writing. Task based activities were used to scaffold language learning. Quantitative data was collected using the Motivation Problem Solving Questionnaire (MPSQ) adapted from Shek et.al (2007) and Mori (2004) as well as from a post-test essay written in class. Supporting qualitative data was also collected through a standardized reflection worksheet as well as through a focus group interview at the end of the treatment period. Three main hypotheses were created based on three dependent variables: perceived problem-solving skills, motivation and writing achievement. The Independent samples t-tests and the One-way MANOVA carried out to investigate the effects of the PSA on perceived problem-solving skills found one sub-skill: behavioral competence to be statistically different between the control group and the treatment group. The independent sample t-test conducted to compare behavioral competence mean scores between groups indicated a significant difference between the treatment group (M = 20.64, SD= 1.96) and the control group (M=18.62, SD= 3.42); (t (55) = 2.71, p<0.01).The magnitude of the differences in the means (mean difference =2.02, 95% CI: .53 to 3.51) was large (eta squared = 0.11). The One-way MANOVA found no statistically significant difference between groups for the combined dependent variables, F(4, 52) p=2.08, p = .09; Wilk’sLamda = .86; partial eta squared = .13. When the results for the dependent variables were considered separately, behavioral competence was found to reach statistical significance, using a Bonferonni adjusted alpha level of 0.01, F(1, 55) = 7.39, p <0.01, partial eta squared =0 .11. Profile plots show an increase for the mean scores for self- determination, resilience and cognitive competence in the treatment group that were not statistically significant. Qualitative data showed that the problem-solving activities helped the participants become better problem solvers as they felt they had become more creative and open-minded to different ideas that might solve the given problem. The Independent samples t-tests and the One-way MANOVA carried out to investigate the effects of the PSA on motivation found one sub-construct: intrinsic motivation to be statistically different between the control group and the treatment group. The independent sample t-test conducted to compare mean scores for intrinsic motivation between groups indicated a significant difference between the treatment group (M = 25.96, SD= 2.54) and the control group (M=23.83, SD=3.00 ; (t(55) = 2.89, p < .01). The magnitude of the differences in the means (mean difference = 2.14, 95% CI: .66 to 3.61) was large (eta squared = 0.13). The one-way MANOVA performed to confirm the results of the independent samples t-test found a statistically significant difference between groups for the combined dependent variables, F(4, 52) p=2.70, p < 0.05; Wilk’sLamda = .82; partial eta squared = .17. When the results for the dependent variables were considered separately, intrinsic motivation was found to reach statistical significance, using a Bonferonni adjusted alpha level of 0.01, F(1, 55) = 8.35, p <0.01, partial eta squared = .13. The profile plots also indicated increases in the mean scores for the treatment group that were not statistically significant for the other three sub-constructs of motivation. Supporting qualitative data revealed that participants liked working in groups as the activities allowed them to interact and work together to solve the problem and complete the writing assignments. Writing achievement scores were found to be significantly different between the treatment and control group (p<.05). After adjusting for pre-treatment scores, results indicated a significant difference between the treatment group and the control group on writing achievement F (1, 54) =10.61, p<0.05, partial eta squared = .16. Supporting qualitative data indicated that the participants liked the PSA as it allowed peer learning and peer correction. They also felt that the PSA made them more open and accepting of other people’s perspectives and improved their writing skills. Finally, the treatment group felt that group ideas and group work enabled them to write better and more organized essays individually. This research provides evidence that the PSA can affect problem-solving skills and sustain motivation levels in International students who are EFL learners. Writing achievement can also be improved. In essence, the PSA provides an effective problem-solving teaching approach that reinforces teacher input and encourages peer learning based on constructivist principles in challenging environments where learners are most likely to experience adjustment and language problems in their host country.